2021
DOI: 10.3389/fnagi.2021.727763
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Bidirectional Associations Between Short or Long Sleep Duration and Lower Cognitive Function: A 7-Year Cohort Study in China

Abstract: Background: Sleep duration is linked to cognitive function, but whether short or prolonged sleep duration results from impaired cognition or vice versa has been controversial in previous studies. We aimed to investigate the bidirectional association between sleep duration and cognitive function in older Chinese participants.Methods: Data were obtained from a nationally representative study conducted in China. A total of 7984 participants aged 45 years or older were assessed at baseline between June 2011 and Ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Multivariable modified Poisson regression analysis in individuals during the period of menopausal transition revealed that the prevalence of severe complaints of reduced cognitive functioning was significantly higher in women with uncertain status and who were postmenopausal, those with short sleeping hours, who worked night-shifts, and had severe VMS. Although short sleeping hours and night-shift work do not necessarily cause cognitive complaints, Hue et al found a bidirectional relationship between sleep duration and cognitive function in a cohort study [ 18 ].The strong association with severe VMS suggests that the cognitive complaints during menopausal transition may in part be related to severe VMS. Current HRT use was not associated with complaints of reduced cognitive functioning in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable modified Poisson regression analysis in individuals during the period of menopausal transition revealed that the prevalence of severe complaints of reduced cognitive functioning was significantly higher in women with uncertain status and who were postmenopausal, those with short sleeping hours, who worked night-shifts, and had severe VMS. Although short sleeping hours and night-shift work do not necessarily cause cognitive complaints, Hue et al found a bidirectional relationship between sleep duration and cognitive function in a cohort study [ 18 ].The strong association with severe VMS suggests that the cognitive complaints during menopausal transition may in part be related to severe VMS. Current HRT use was not associated with complaints of reduced cognitive functioning in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to sleep deprivation, previous studies have revealed that an excessively long sleep duration is associated with increased risks for cognitive decline and various diseases as well as death in the elderly population (Cappuccio et al, 2010;Shen et al, 2016;Yin et al, 2017;Jike et al, 2018;Ohara et al, 2018;Ma et al, 2020;Hua et al, 2021); a U-shaped association between sleep duration and cognitive function is a common finding among recent studies. Based on those findings, the National Sleep Foundation has announced that deviation from an ideal sleep duration-<5 h or more than 9 h for elderly people-is not recommended for individuals who are 65 years and older (Hirshkowitz et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…Short sleep duration contributes to cognitive impairment via several different pathologies such as impaired β-amyloid clearance, pathological tau, impaired synaptic plasticity, atrophy of the cortex, and circadian rhythm disturbances. In contrast, long sleep duration is relevant to sleep fragmentation and chronic inflammation, which are linked to lower cognition ( 46 ). Moreover, Spira et al ( 47 ) demonstrated that, among individuals with a normal cognitive function, sleep durations of < 7 h and of >7 h may accelerate frontotemporal gray matter atrophy and subsequently increase the cognitive impairment risk.…”
Section: Discussionmentioning
confidence: 99%